PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Harianto, Harianto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This study aimed to test whether capital structure consisting of Debt Ratio (DR) , Debt Equity Ratio (DER) andFinancial Performance comprised of Earning Per Share (EPS) , Return on Equity (ROE) affect the Stock Price .The population in this study is a manufacturing company that listed its shares on the Indonesia Stock Exchange(BEI) in 2006-2010 . The sampling technique used in this study is the purposive sampling in which the samplewas selected on the basis of certain considerations or criteria and the number of samples obtained in the studywas 16 Textile and Garment companies listed in Indonesia Stock Exchange (BEI). The results showed that : (1)Debt Ratio (DR) significantly affects stock price (HS) , (2 ) Debt Equity Ratio (DER) significantly affects StockPrice (HS) , (3) Earning Per Share (EPS) significantly affects Stock Price (HS) , (4) Return on Equity (ROE)significantly affects Stock Price (HS) , (5) Capital Structure and Financial Performance berengaruhsimultaneously significantly on Stock Price (HS)Keywords : capital structure ratios and financial performance , multiple linear regression analysisand the positive influence, stock price